(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The aphelinid parasitoids, Aphytis paramaculicornis DeBach & Rosen, A. chrysomphali (Mercet) and Encarsia aurantii (Howard) (Hymenoptera: Aphelinidae) were mass reared and released at monthly intervals in olive groves infested with Parlatoria oleae (Colvee) at five locations in Egypt. A total of about 115,000 adult parasitoids were augmentatively released between March 2000 and Feb. 2001. Although the percentage parasitism of the scale increased in the experimental plots compared with the control plots after parasitoid release, there was no apparent reductions in the scale populations at any site. Only E. aurantii populations continued to increase during the months March through to September and this appeared to be the parasitoid best adapted to attack the P. oleae populations when they were near their peak; however, it did not become established at two of the sites. It is concluded that further augmentative releases are unlikely to improve the present biological control of P. oleae at any of these sites.